Managing packaged tourism : relationships, responsibilities and service quality in the inclusive holiday industry - Laws, Eric. (International Thomson Business Press, 1997)
This book is divided into five parts: The evolution and structure of the inclusive holiday industry; Analysing the inclusive holiday industry; Marketing and distributing inclusive holidays; Creating and operating inclusive holidays; and The timeshare industry.